Management of Classical Islamic Renewal to the Modern Era in the Muhammadiyah Context: Manajemen Pembaharuan Pendidikan Islam Klasik Ke Era Modern Dalam Konteks Muhammadiyah - Wakit , Saipul; Suyitno, Margiyono; Dacholfany, Muhammad Ihsan (Halaqa: Islamic Education Journal, 2024)
This research analyzes the renewal of classical Islam from an educational perspective in Muhammadiyah, an Islamic organization in Indonesia. Through an interdisciplinary approach, this research explores the historical background and objectives of the reform movement, as well as its impact on the world of Muslim education. Muhammadiyah, as a movement that was born at the beginning of the 20th century, faced the context of the challenges of colonialism, intellectual stagnation, and the need for reform of Islamic teachings. Muhammadiyah's role was in responding to the social and intellectual conditions of its time by bringing the spirit of tajdid and ijtihad into Islamic education. The research method uses library research with a qualitative approach by comparing data findings with current phenomena in the field. The findings are narrated in a qualitative discussion using credible words. The research results explain that by focusing on curriculum renewal, an inclusive approach, and instilling a critical spirit in Islamic thought, Muhammadiyah is trying to create a relevant and progressive educational environment. The implications of this reform are also analyzed in the context of its impact on the thinking and character of Muslims in the modern world. Substantially, the results of this research provide in-depth insight into how Muhammadiyah plays a role in refreshing and updating classical Islamic teachings through the education system, and how its contribution influences the thinking and character of Muslims in the dynamics of the contemporary world of education.